Developmental programming for allergy: a secondary analysis of the Mothers, Omega-3, and Mental Health Study - Romero, Vivian C.; Somers, Emily C.; Stolberg, Valerie; Clinton, Chelsea; Chensue, Stephen; Djuric, Zora; Berman, Deborah R.; Treadwell, Marjorie C.; Vahratian, Anjel M.; Mozurkewich, Ellen (American journal of obstetrics and gynecology, 2013)
Fetal dysregulation of T helper cell pathways may predispose to allergy, as high cord blood T helper 2/T helper 1 ratios have been shown to precede development of allergic diseases. We aimed to determine whether prenatal eicosapentaenoic acid and docosahexaenoic acid supplementation reduces T helper 2 to T helper 1-associated chemokine ratios. We also explored the effect of mode of delivery on T helper 2/T helper 1 ratios. We conducted a secondary analysis of a randomized placebo controlled trial initially performed to assess the effects of docosahexaenoic acid or eicosapentaenoic acid supplementation on pregnancy-related depressive symptoms among 126 participants. Cord plasma specimens from 98 newborns were assayed for chemokines associated with T helper 2 (thymus and activation-regulated chemokine [CCL17], macrophage-derived chemokine [CCL22], eotaxin [CCL 11]) and T helper 1 (interferon-inducible protein-10 [CXCL 10]) by enzyme-linked immunosorbent assay and Multiplex immunoassays. Ratios of log-transformed chemokines macrophage-derived chemokine/interferon-inducible protein-10 and thymus and activation-regulated chemokine/interferon-inducible protein-10 were compared between groups by analyses of variance. Multiple linear regression was performed to examine associations between treatments and chemokine ratios, adjusting for covariates. After adjusting for gestational age at delivery, birthweight, and mode of delivery, both omega-3 supplementation groups were associated with lower macrophage-derived chemokine/interferon-inducible protein-10 ratios than placebo (eicosapentaenoic acid: coefficient −1.8; 95% confidence interval [CI], −3.6 to −0.05; P = .04; docosahexaenoic acid: −2.0; 95% CI, −3.9 to −0.07; P = .04). Similar associations were found for thymus and activation-regulated chemokine/interferon-inducible protein-10 (eicosapentaenoic acid: −1.5; 95% CI, −3.0 to 0.06; P = .06; docosahexaenoic acid −2.2; 95% CI, −3.8 to −0.52; P = .01). Cesarean delivery was associated with higher macrophage-derived chemokine/interferon-inducible protein-10 (1.6; 95% CI, 0.01−3.3; P = .049) and thymus and activation-regulated chemokine/interferon-inducible protein-10 (1.5; 95% CI, 0.1−2.9; P = .042) ratios than vaginal delivery. Prenatal supplementation with eicosapentaenoic acid and docosahexaenoic acid resulted in decreased cord blood T helper 2/T helper 1 chemokine ratios. Cesarean delivery was associated with a pronounced T helper 2 deviation at birth.